Apparatus and method of 2D ultrasound manipulation - Goh, Nicholas Guo Hao (Nanyang Technological University, 2025)
Acoustic levitation uses sound waves to hold and levitate matter in mid-air. At times, the matter could be manipulated and moved between a pair of acoustic transducers or a transducer and reflector. While we are familiar with the power of sound for music, sound is used in this research to exert a physical force that would be sufficient to manipulate an object on a testbed. To use this force, acoustic transducers are used in this research to form sound patterns and high-frequency soundwaves, so that the particles could be levitated or manipulated. Through the use of sound waves, researchers have levitated small objects such as insects and individual cell types in the medical field. These actions could allow for scientists and researchers to leverage acoustic levitation and manipulation to work without having to physically be in contact with potentially hazardous particles or objects. Using this method, it also allows for the use of acoustic levitation and manipulation to work like a robot – but with lower cost and possibly higher precision. Currently, only small levitation forces have been generated, although the forces produced could have been much higher. This includes the levitation of heavier objects such as metal components and human in the near future. In the course of this project, we will delve further into the standing wave method of acoustic levitation, the acoustic tweezer method in acoustic manipulation and the acoustic manipulation of Styrofoam particles in a two-dimensional space.